2013
DOI: 10.1093/toxsci/kft187
|View full text |Cite
|
Sign up to set email alerts
|

Relating Cytotoxicity, Zinc Ions, and Reactive Oxygen in ZnO Nanoparticle–Exposed Human Immune Cells

Abstract: Although zinc oxide (ZnO) nanoparticles (NPs) have been widely formulated in sunscreens, the relationship between reactive oxygen species (ROS) generation induced by these particles, zinc ions, and cytotoxicity is not clearly understood. This study explores whether these factors can be accurately quantified and related. The study demonstrates a strong correlation between ZnO NP-induced cytotoxicity and free intracellular zinc concentration (R (2) = .945) in human immune cells, indicating a requirement for NP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
155
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(168 citation statements)
references
References 37 publications
12
155
0
1
Order By: Relevance
“…The zinc ions might explain ZnO-induced cytotoxic and apoptotic activity. Zinc ions released from ZnO materials induce oxidative stressmediated cell death [7][8][9], and the strong correlation between ZnO NPs-induced cytotoxicity and free zinc ion concentration also suggests a requirement for ZnO dissolution for effective cytotoxicity [10]. A number of studies have reported the toxicity of ZnO materials, and their potential to induce cell death has been explored in cancer biology [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…The zinc ions might explain ZnO-induced cytotoxic and apoptotic activity. Zinc ions released from ZnO materials induce oxidative stressmediated cell death [7][8][9], and the strong correlation between ZnO NPs-induced cytotoxicity and free zinc ion concentration also suggests a requirement for ZnO dissolution for effective cytotoxicity [10]. A number of studies have reported the toxicity of ZnO materials, and their potential to induce cell death has been explored in cancer biology [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticles were located exclusively in the cytoplasmic region. Shen et al 52 have reported cytotoxicity of ZnO nanoparticles on human immune cells. Their study shows a strong correlation between the cytotoxicity induced by ZnO nanoparticles and free intracellular zinc concentration.…”
Section: Cytotoxicity Of Nanomaterialsmentioning
confidence: 99%
“…Therefore, the toxicity of ZnO NPs is thought to be attributed to the NPs themselves. It also has been suggested that Zn ions released from ZnO NPs form zincphosphate-carbonate nanosized precipitate in culture medium (Turney et al, 2012), and this precipitate might protect cells from extracellular soluble zinc (Shen et al, 2013).…”
Section: Effect Of Zn Ions Released From Zno Nps On the Toxicity Of Tmentioning
confidence: 99%
“…ZnO induces protective proteins, such as methallothioneins, against oxidative stress, and is occupied by the protective proteins. This occupation results in free transition metal ions, such as iron and copper, which induces a Fentontype reaction and increases ROS production (Krezel et al, 2007;Shen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation